Hubungan Menggendong Posisi M-Shape Terhadap Bounding Attachment dan Kualitas Tidur Pada Bayi Berusia 3-6 Bulan di Posyandu Cemara III Desa Rahuning Tahun 2023 - Lia Aprianti; Tiarnida Nababan; Hosanna Angelika Panjaitan; Romana Yutrianis Bali (Universitas Pahlawan Tuanku Tambusai, 2023)
Infancy is a golden period for the growth and development of children so it needs special attention and affection. One of the factors that affect the growth and development of the baby is sleep and rest. One way that can be used to meet these needs is to hold the baby. However, the reality shows that there are still many mothers who are reluctant to carry their babies routinely, especially at the beginning of birth. This is because there is a feeling of fear of holding the baby wrong and not knowing how to hold the baby in the correct position. The M-Shape position is currently considered the safest because it keeps the baby's pelvis in its cavity and avoids hip dysplasia. This study aims to analyze the relationship between holding the M-Shape position on bounding attachment and sleep quality in infants aged 3-6 months at Posyandu Cemara III Rahuning Village. The type of research used is a quasi experiment with the design